The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2021.629761
|View full text |Cite
|
Sign up to set email alerts
|

Considerations and Perspectives on Interventions to Improve Social Cognition in Adolescents With ASD Without ID: Involving Parents in Social Skills Groups

Abstract: Improving social cognition and social skills is a challenge faced by individuals with Autism Spectrum Disorder without Intellectual Disability at any age. This process is particularly critical during late adolescence (15–18 years), a developmental phase generally characterized by rich social experiences that usually foster the development of friendships. Nevertheless, for youth with ASD, lingering difficulties in social cognition often hinder their ability to generate responses considered socially appropriated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…In a reflection piece on the PEERS social skills programme translated into French. Vuattoux et al (2021) also identified the importance of parental involvement in the maintenance of improvements in adolescents (aged 15-18 with ASD without ID) on social responsiveness, social knowledge, and social reciprocity [69]. Parents acted as agents of reinforcement and generalisation of the acquired knowledge.…”
Section: The Requirements Of Ssis For Thai Adolescents With Asdmentioning
confidence: 99%
“…In a reflection piece on the PEERS social skills programme translated into French. Vuattoux et al (2021) also identified the importance of parental involvement in the maintenance of improvements in adolescents (aged 15-18 with ASD without ID) on social responsiveness, social knowledge, and social reciprocity [69]. Parents acted as agents of reinforcement and generalisation of the acquired knowledge.…”
Section: The Requirements Of Ssis For Thai Adolescents With Asdmentioning
confidence: 99%